Impact of control strategies for wind-assisted ships on energy consumption - Cem Guzelbulut; Timoteo Badalotti; Katsuyuki Suzuki (Brodogradnja)
Wind-assisted ship propulsion is one of the solutions for reducing greenhouse gas emissions by generating additional thrust using renewable wind power. Various technologies utilizing wind power to generate thrust are being developed and adopted by the industry. In addition to the thrust, side forces are also generated as secondary outputs, and they significantly affect ship motion. Although many studies have been conducted on the effects of sails on ship dynamics and energy consumption, the impact of control strategies of wind-assisted ships on energy consumption has not been clearly identified. This study aimed to determine the bearings of different control strategies on ships in terms of motion and energy. When the heading control strategy is adopted, rotor sails can reduce energy consumption by up to 10%. However, course- and speed-controlled ships without any wind-assistance devices can reduce energy consumption by 15%, and a further reduction of up to 30% can be achieved through rotor sails depending on the wind direction. When the control of the rotor sails was changed from a stand-alone controller to a ship dynamics-integrated controller, the energy consumption can be reduced by approximately 1-2% for course- and speed-controlled ships.